Implementasi Kebijakan E-Order Pada Transaksi Pengadaan Langsung Dengan UMKM Di Provinsi Dki Jakarta - OKI SULISTIYO; A. H. Rahadian (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This study aims to find out how the description of policy implementation through direct procurement through the e-order system which was launched on January 7 2020, what are the benefits for business actors, especially MSMEs in DKI Jakarta and how effective it is for SKPD / SKPD Units in procuring goods. This type of research is descriptive qualitative research. With informants who deal directly with procurement directly through the e-order system. Data was collected through observation, interviews and documentation. Data analysis techniques used in this study include data reduction, display, conclusion, and verification. Based on the results of this research and data processing, it can be concluded that the implementation of direct procurement through the e-order system has been going well, there are only a few obstacles in the process, such as lack of knowledge due to lack of socialization in electronic procurement in DKI Jakarta Province, especially the Central Jakarta Administrative City Area.